2020
DOI: 10.33711/yyuefd.691498
|View full text |Cite
|
Sign up to set email alerts
|

Çocukların Dijital Oyun Bağımlılığına Göre Aile Profillerinin Belirlenmesi

Abstract: In this study, it is aimed to determine family profiles of children based on their digital game addiction. Firstly, digital gaming addiction scale was applied to children and digital game addiction levels of children were determined. Then, Qualitative data were gathered through semi-structured interviews with the parents of the children who have the highest and the lowest gaming addiction scores at digital game addiction scale. The sample of the study consisted of the children who were attending in the seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 9 publications
1
10
0
10
Order By: Relevance
“…According to the findings of this study, as the perceived social support of adolescents decreases, online game addiction increases. This finding is supported by similar studies in the literature (Ayas & Horzum, 2013;Baysak et al, 2018;Bonnaire & Phan, 2017;Durak-Batıgün & Kılıç, 2011;Günüç & Doğan, 2013;Karaer & Akdemir, 2019;Özmen, 2019;Öztosun, 2018;Varol-Afo, & Mortan Sevi, 2019;Yeh et al, 2008;Yiğit & Günüç, 2020). With low family support and neglect of children in particular, (Sussman et al, 2014;Beyazıt & Bütün Ayhan, 2019), conflicts and problems in family relationships (Boannaire & Phan, 2017;Çalışkan & Özbay, 2015;Yiğit & Günüç, 2020) and the absence of one of the parents (Taechoyotin, Tongro, & Piyaraj, 2018) significantly correlate with video game addiction.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to the findings of this study, as the perceived social support of adolescents decreases, online game addiction increases. This finding is supported by similar studies in the literature (Ayas & Horzum, 2013;Baysak et al, 2018;Bonnaire & Phan, 2017;Durak-Batıgün & Kılıç, 2011;Günüç & Doğan, 2013;Karaer & Akdemir, 2019;Özmen, 2019;Öztosun, 2018;Varol-Afo, & Mortan Sevi, 2019;Yeh et al, 2008;Yiğit & Günüç, 2020). With low family support and neglect of children in particular, (Sussman et al, 2014;Beyazıt & Bütün Ayhan, 2019), conflicts and problems in family relationships (Boannaire & Phan, 2017;Çalışkan & Özbay, 2015;Yiğit & Günüç, 2020) and the absence of one of the parents (Taechoyotin, Tongro, & Piyaraj, 2018) significantly correlate with video game addiction.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…Video game addiction is defined as excessive and problematic use of video games and computers to such an extreme extent that it causes social and emotional problems (Lemmens, Valkenburg, & Peter, 2009, p.78). It is understood that video game addiction in Turkey varies between 2.1% (Yalçın- Irmak & Erdoğan, 2015), 3.7% (Arıcak et al, 2019), 11.6% (Baysak et al, 2016), and 15% (Yiğit & Günüç, 2020). In Weinstein's study (2010), ong term changes in the reward circuitry can be caused by playing computer games and it can show effects resembling those of substance dependence.…”
Section: Introduction 107mentioning
confidence: 99%
“…Today, technology shows its presence in the lives of people of all age groups, specifically children and young people who use technology widely (Yiğit & Günüç, 2020). One of the areas of technology that develops day by day, adding new ones on top of the old ones and making daily life easier, is information technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Parents should guide their children instead of restricting their use of technology, and raise awareness of their children about the benefits and harms of the internet (Zeybekoğlu Akbaş & Dursun, 2020). According to the research conducted by Yiğit and Günüç (2020), families are categorized as families whose children are addicted to digital games, whose children are not addicted to digital games, and who are in the risk group. According to the study, it was concluded that parents whose children are addicted to digital games could not communicate properly with their children.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals need to be equipped with digital literacy to be successful in the digital age and to be equipped alongside the developments in the future (Terkan & Taylan, 2010). Today, technology exists in human lives of all ages and especially children and young people commonly use technology (Yigit & Gunuc, 2020). One of the fields of technology that develops each day and facilitates daily life by adding something new to itself is information technologies.…”
Section: Introductionmentioning
confidence: 99%